Effects of ripple cross angles and turbulence models on wet curtain resistance - Ding, Tao; Fang, Lumeng; Shi, Zhengxiang; Li, Baoming; Zhao, Yang (International Journal of Agricultural and Biological Engineering, 2019)
To study the influence of ripple cross angles on the resistance of wet curtains, wet curtains with different ripple cross angles (45°/45°, 45°/15°) were tested on agricultural ventilation equipment performance testing benches, and the static pressure drop under different wind speeds (1-3 m/s) was determined. Four turbulence models (κ-ε, RNG κ-ε, κ-ω, SST κ-ω) were adopted for numerical simulations of the two types of wet curtain, and the simulations’ results were compared with those of experiments. The average errors found are 41.1%, 48.7%, 27.1%, and 27.8%, respectively, and the κ-ω model is found to be the most suitable one for the calculation of wet curtain resistance among the four turbulence models. By using the κ-ω turbulence model, the static pressure drop performances of wet curtains with ripple cross angles 45°/35° and 45°/25° were calculated. Resistance increases with wind speed and ripple cross angles, and a large ripple cross angle has a higher resistance growth rate with increasing wind speed.Keywords: wet curtain, ripple cross angle, resistance, turbulence model, ventilation, cooling and humidifying systemDOI: 10.25165/j.ijabe.20191204.3446Citation: Ding T, Fang L M, Shi Z X, Li B M, ZhaoY. Effects of ripple cross angles and turbulence models on wet curtain resistance. Int J Agric & Biol Eng, 2019; 12(4): 43–46.